2021
DOI: 10.3390/polym13244450
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Crystal Structure and Mechanical Performance for Fabrication of Regenerated Cellulose Film through Coagulation Conditions

Abstract: Cellulose films regenerated from aqueous alkali–urea solution possess different properties depending on coagulation conditions. However, the correlation between coagulant species and properties of regenerated cellulose (RC) films has not been clarified yet. In this study, RC films were prepared from cellulose nanofiber (CNF) and microcrystalline cellulose (MCC) under several coagulation conditions. Cellulose dissolved in aqueous LiOH–urea solution was regenerated using various solvents at ambient temperature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…From Figure b, it can be observed that wood pulp cellulose exhibited the type I crystal structure, as its peaks were at 23.0, 15.0, and 17.0°. Generally speaking, the crystal structure of cellulose regenerated from ILs was type II, , but the addition of DMSO in the solvent resulted in the formation of an amorphous crystal structure in Q-RCFs, with the main crystal plane observed at 21.3°. Additionally, the regenerated quercetin from the two ILs exhibited different structural characteristics. The use of [Emim]­DEP ensured that the crystal structure of regenerated quercetin remained the same as natural quercetin, as evident from the peaks observed at 8–18 and 23–30°. ,, On the other hand, the quercetin regenerated from [Emim]Ac did not show any peaks, indicating the loss of its crystalline features.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure b, it can be observed that wood pulp cellulose exhibited the type I crystal structure, as its peaks were at 23.0, 15.0, and 17.0°. Generally speaking, the crystal structure of cellulose regenerated from ILs was type II, , but the addition of DMSO in the solvent resulted in the formation of an amorphous crystal structure in Q-RCFs, with the main crystal plane observed at 21.3°. Additionally, the regenerated quercetin from the two ILs exhibited different structural characteristics. The use of [Emim]­DEP ensured that the crystal structure of regenerated quercetin remained the same as natural quercetin, as evident from the peaks observed at 8–18 and 23–30°. ,, On the other hand, the quercetin regenerated from [Emim]Ac did not show any peaks, indicating the loss of its crystalline features.…”
Section: Resultsmentioning
confidence: 99%
“…The main diffraction peaks appear at 2 θ = 20° and 22.1°, corresponding to the (110) and (020) crystal planes, respectively, which are supposed to represent the typical cellulose II crystal structure [ 44 , 45 ]. The peaks corresponding to (110) and (020) are formed by inter- and intra-hydrogen bonding [ 46 ], proposing a hydrogen-bonded network in cellulose [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The RC film was prepared following the procedure described in our previous report. 39 The mixture composed of LiOH, urea, and H 2 O with a weight ratio of 4.6:15.0:80.4, containing CNF slurry, was cooled at −14 °C for an hour. Concentration of CNF was adjusted at 3 wt %.…”
Section: Materials and Methodsmentioning
confidence: 99%